Evaluation of leaks and passes in reboilers of a natural gas liquids fractionation plant - Calvo, Carlos Sebastián (2019)
In recent years, it has been developed various techniques based on the applicationof tracers and radiation sources to solve problems operating facilities oil refining andgas.In this case, a series of determinations are reported with a series of experiencesradiotracers a fractionation plant natural gas liquid in Peru, for leaks / passes thatcould exist in three reboilers different processing units.The tracer technique for online detection was used, by using two radiotracerdepending on the phase to be investigated: oleic acid labeled with Iodine 131 asa radiotracer for the hydrocarbon phase and an aqueous solution of iodine 131 forthe aqueous phase, when necessary. A data acquisition system, a portable PC, anddetectors in proper positions were used. Recording values were synchronized as wellas ambient background, prior to each injection of radiotracer. Radiation counts wererecorded at intervals of 1 second, depending on each case.Six determinations were conducted by six injection of radiotracer incorporated,either in tubes or shell, as applicable.We achieved detection limits leakage of 0.1 %, of one stream to another.